Spatial-temporal evolution of land use carbon emissions and influencing factors in Zibo, China - Li, Lijing; Zhang, Xiaoping; Yu, Lu; Xiao, Huabin (Frontiers in Environmental Science, 2024)
The global climate crisis is escalating, and how to reduce land use carbon emission (LUCE) while promoting social and economic development is a global issue. The purpose of this study was to investigate the spatio-temporal evolution characteristics and influencing factors of LUCE at the county scale. To accomplish this goal, based on Zibo County land use data and societal energy consumption statistics, for predicting the net LUCE in 2010, 2015, and 2020. GIS spatial analysis and spatial autocorrelation model were utilized to investigate the spatio-temporal evolution characteristics of LUCE. The geographical and temporal weighted regression (GTWR) model was used to investigate the influencing factors and spatial differences. The findings demonstrate that: (1) the rate of land use change in Zibo City decreased between 2010 and 2020, with the overall land use motivation falling from 0.14% to 0.09%. The area of arable land, forest land, and grassland decreased, while the amount of water, developed land, and unutilized land increased. Between 2010 and 2020, net carbon emissions in Zibo City increased significantly, from 3.011 × 107tC to 3.911 × 107tC. The spatial distribution of LUCE followed a clear pattern of “elevated in the east and diminished in the west, elevated in the south and diminished in the north.” The spatial agglomeration characteristics of LUCE are obvious, and the overall trend of the Moran I value is falling, from 0.219 to 0.212. The elements that determine LUCE vary greatly by location, with the most major influences being, in descending order, energy consumption per unit of GDP, urbanization rate, land-use efficiency, and population size. The energy consumption per unit of GDP has the greatest impact on Linzi District, with coefficients ranging from 55.4 to 211.5. The study clearly depicts the spatio-temporal distribution of carbon emissions resulting from land use in Zibo City and the factors that contribute to them. Simultaneously, it provides a scientific framework for improving land use structure and implementing low-carbon programs throughout the region.